2019
DOI: 10.3390/ijms20133214
|View full text |Cite
|
Sign up to set email alerts
|

Absence of MCP-induced Protein 1 Enhances Blood–Brain Barrier Breakdown after Experimental Stroke in Mice

Abstract: Focal cerebral ischemia can cause blood–brain barrier (BBB) breakdown, which is implicated in neuroinflammation and progression of brain damage. Monocyte chemotactic protein 1–induced protein 1 (MCPIP1) is a newly identified zinc-finger protein that negatively regulates inflammatory signaling pathways. We aimed to evaluate the impact of genetic MCPIP1 deletion on BBB breakdown and expression of BBB-related matrix metalloproteinases (MMPs) and tight junction proteins after cerebral ischemia/reperfusion (I/R) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…In addition, we showed that genetic suppression of MCPIP1 abolishes TMP-mediated cell protection, upregulates TNF-α expression, and exacerbates OGD-induced cell death in cultured neurons in vitro . The results obtained from our study are consistent with a recent study showing that genetic knockout of MCPIP1 exacerbates ischemia-induced BBB breakdown and ischemic brain injury ( Jin et al, 2013 ; Jin et al, 2019b ). Other proinflammatory cytokines, like IL-1β, IL-6, and MCP-1, also contribute to the BBB breakdown and subsequent progression of neuron death and dysfunction ( Dimitrijevic et al, 2006 ; Strecker et al, 2011 ; Yao and Tsirka, 2014 ; Amantea et al, 2015 ; Esenwa and Elkind, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we showed that genetic suppression of MCPIP1 abolishes TMP-mediated cell protection, upregulates TNF-α expression, and exacerbates OGD-induced cell death in cultured neurons in vitro . The results obtained from our study are consistent with a recent study showing that genetic knockout of MCPIP1 exacerbates ischemia-induced BBB breakdown and ischemic brain injury ( Jin et al, 2013 ; Jin et al, 2019b ). Other proinflammatory cytokines, like IL-1β, IL-6, and MCP-1, also contribute to the BBB breakdown and subsequent progression of neuron death and dysfunction ( Dimitrijevic et al, 2006 ; Strecker et al, 2011 ; Yao and Tsirka, 2014 ; Amantea et al, 2015 ; Esenwa and Elkind, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…MCPIP1 also functions as a RNase promoting inflammatory mRNA degradation ( Musson et al, 2020 ). In the absence of MCPIP1, the expression of matrix metalloproteinase (which destroys extracellular matrix and destroys the BBB) and the expression of Claudin-5 (integrin of TJs) is decreased, which aggravates BBB destruction ( Jin et al, 2019 ). In addition to MCPIP1-mediated inflammatory responses, ZEB1 (C2H2 type) in microglia after ischemic stroke can reduce neutrophils infiltration into ischemic brain by reducing the production of C-X-C motif ligand 1 (CXCL1) in astrocytes (CXCL1 is a chemokine that mainly absorbed neutrophil), thereby alleviating nerve injury ( Li et al, 2018 ).…”
Section: Role Of Zinc Finger Proteins In Neuro-related Diseasesmentioning
confidence: 99%
“…Another study has shown that TRAIL-R2 is one of the most powerful biomarkers for predicting long-term mortality in many diseases, such as diabetes, heart failure, myocardial infarction, smoking, and hypercholesterolemia [153]. MCPIP1 has recently been shown to negatively regulate inflammatory responses after ischemic stroke, to enhance blood-brain barrier integrity, and to be neuroprotective [154]. Additionally, RBM3 has recently been shown to be neuroprotective and positively correlate with good ischemic stroke outcomes [155].…”
Section: Let-7's Protein Regulators and Their Role In Stroke And Other Cardiovascularmentioning
confidence: 99%